The AST/ALT Ratio (De Ritis Ratio) Represents an Unfavorable Prognosis in Patients in Early-Stage SFTS: An Observational Cohort Study - Wang, Lianzi; Xu, Yang; Zhang, Shubing; Bibi, Asma; Xu, Yuanhong; Li, Tao (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Severe fever with thrombocytopenia syndrome (SFTS), a widely prevalent infectious disease caused by severe fever with thrombocytopenia syndrome virus (SFTSV) that carries with it a high mortality rate, has emerged to be a public health concern. This study aimed to investigate the epidemiological and clinical characteristics of patients infected with SFTSV, seeking novel prognostic risk factors for SFTS. Methods: In this retrospective and cross-sectional study, confirmed SFTS patients from the First Affiliated Hospital of Anhui Medical University were enrolled from September 1, 2019 to December 12, 2020. Cases were analyzed for epidemiological, demographic, clinical, and laboratory data. Logistic regression models were used to assess the association between predictors and outcome variables. A generalized additive mixed model (GAMM) was conducted to analyze the trending shift of aspartate aminotransferase/alanine transaminase-ratio (AST/ALT-ratio) and platelet (PLT) in SFTS patients treated with ribavirin. p values ≤ 0.05 were considered statistically significant. Results: Clinical and laboratory results of 107 hospitalized patients with SFTSV infection were retrospectively described. Mean age at onset of disease was 60.38±11.29 years old and the ratio between male and female was 1:1.2. Fever and thrombocytopenia were hallmark feature of SFTS. Furthermore, multiple cases also experienced neurological complications, gastrointestinal / skeletal muscle symptoms together with other non-specific clinical manifestations, laboratory dataset outcomes reported dysregulated levels for routine blood biomarkers, coagulation function and biochemistry. Overall, 107 patients were segregated into two group according patient condition at clinical endpoint (survivors / non-survivors). SFTS survivors had a higher level of PLT- counts, total protein (TP) and estimated glomerular filtration rate (eGFR), while levels of activated partial thromboplastin time (APTT), thrombin time (TT), D-dimer (D-D), fibrinogen degradation products (FDP), ALT, AST, AST/ALT-ratio, creatinine (Cr), creatine phosphokinase (CK) and procalcitonin (PCT) was higher in non-survivors. Results from univariate cox regression revealed that elevated levels of FDP, TT, AST/ALT-ratio, PCT, as well as decreased eGFR level and presence of central nervous system symptoms (CNS), were significant predictors for SFTS prognostic, results from multivariate logistic regression analysis in three adjusted models showed AST/ALT-ratio and PCT were independent risk factor for the prognosis of SFTS patients.